Whistblowing as an Employee Unmasking in the Human Resource Management - Andrzejewski, Marek (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The study of pathology and dysfunction of the organization involved in the analysis and evaluation of the deviation, then the theoretical generalization, and determination of their remedies. Article presents an analysis and evaluation of pathology in the management of selected, namely corruption and anomie employees. Decision was an attempt to identify the employee as an unmasking remedy human resources management in Poland. The effective way to eliminate various types of pathology in the organization has spread throughout the world. In Poland, for various reasons is not proper and expected use of the facts to a significant increase in the number and impact of pathology and dysfunction in the organizations.